HUBUNGAN PARITAS DENGAN SIKAP IBU HAMIL TENTANG KUNJUNGAN KEHAMILAN K1 MURNI DI DESA TANAMERAH KECAMATAN SARONGGI KABUPATEN SUMENEP - Dian Permatasari; Eva Nurhidayati (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2016)
Pure K1 coverage is an indicator to know the reach of ANC services to achieve the optimum degree of health especially in pregnancy examination in order to recognize early complications. In fact, there are still many pregnant women who do not do Pure K1, such as coverage of K1 Murni in Tanamerah Village Working Area of ​​UPT Puskesmas Saronggi 53% from target 87% until November. The purpose of this research is to know the relation of parity with attitude of pregnant mother about visit of Antenatal care K1 Murni. The research design was correlational analitic with cross sectional study approach. The population is 46 pregnant women in Tanamerah Saronggi Village from April to May 2014.Total population is 46 respondents. Variable independent is parity and variable dependent is the attitude of pregnant mother in doing visit of pregnancy of K1 Murni. Methods of collecting data in the form of questionnaires and cohorts and then analyzed by statistical test Rank Rank Wilcoxone with α = 0.05. Most of pregnant women had more than 1 (Multipara), 34 respondents (73,9%) and most pregnant women were negative about Pure K1 pregnancy, 33 respondents (71,7%). With significance test (p) 0.002 which means p <α. Based on the research results can be concluded there is a parity relationship with the attitude of pregnant women to visit pregnancy K1 Murni in Tanamerah Village Work Area UPT Puskesmas Saronggi District Saronggi Sumenep Regency. Pregnant women and families should increase their willingness and awareness to check their pregnancy according to ANC standard.